2007
DOI: 10.1016/j.cellbi.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taxol treatment on the microtubular system and mitochondria of Tetrahymena

Abstract: Complex investigation was done using immunocytochemical confocal microscopy, electron microscopy and flow cytometry on the effect of taxol to the microtubular arrangement and dynamics. The most interesting phenomenon was the rapid disappearance of transversal microtubule bands, while longitudinal microtubule bands remained and were submitted to the known effects of taxol. There was a broad variation in mitochondrial effect, some of them remained normal, while others swollen, desintegrated and their tubules dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It is well known that secondary metabolites play a major role in the adaptation of plants to the changing environment and in overcoming stress constraints, and higher concentrations of secondary metabolites might result in a more resistant plant, but the production of secondary metabolites is thought to be costly and reduces plant growth and reproduction (Siemens et al 2002). Paclitaxel is a cytotoxic substance that inhibits cell proliferation by binding to the microtubule surface, specifically to the subunits of the tubulin heterodimers, thus promoting tubulin depolymerization (Kovács et al 2007). Kim et al (2004) found that cell cultures of high paclitaxel producing Taxus cells demonstrated growth inhibition upon subculture, whereas non-paclitaxel producing ones demonstrated little growth inhibition; therefore, the group speculated that growth inhibition was primarily due to paclitaxel or taxane accumulation.…”
Section: S3mentioning
confidence: 99%
“…It is well known that secondary metabolites play a major role in the adaptation of plants to the changing environment and in overcoming stress constraints, and higher concentrations of secondary metabolites might result in a more resistant plant, but the production of secondary metabolites is thought to be costly and reduces plant growth and reproduction (Siemens et al 2002). Paclitaxel is a cytotoxic substance that inhibits cell proliferation by binding to the microtubule surface, specifically to the subunits of the tubulin heterodimers, thus promoting tubulin depolymerization (Kovács et al 2007). Kim et al (2004) found that cell cultures of high paclitaxel producing Taxus cells demonstrated growth inhibition upon subculture, whereas non-paclitaxel producing ones demonstrated little growth inhibition; therefore, the group speculated that growth inhibition was primarily due to paclitaxel or taxane accumulation.…”
Section: S3mentioning
confidence: 99%
“…Therefore, chemotherapy is still the mainstay of systemic treatment for TNBC [6]. Paclitaxel is a mitotic inhibitor-based chemotherapeutic drug [8, 9], due to its high efficiency, and is widely used to treat TNBC. Unfortunately, drug resistance is still a major hurdle in the use of paclitaxel and limits its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…It received wide attention recently because its leaves and bark were found to be the prime source of taxol, a potent anticancer drug which has a unique property of preventing the growth of cancerous cells and is used in the treatment of breast and ovarian cancers. [4] Taxol was first isolated from the bark of Taxus brevifolia ,[5] and since then, taxol and related bioactive taxoids have been reported from various other species of the genus Taxus. [67] Excellent clinical results with taxol in the treatment of various cancers, particularly in refractory ovarian and breast cancers, have led to substantial demand for this drug.…”
Section: Introductionmentioning
confidence: 99%